2004
DOI: 10.1051/vetres:2004026
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in research into the Cyathostominae and Anoplocephala perfoliata

Abstract: -Intestinal helminths are an important cause of equine disease. Of these parasites, the Cyathostominae are the commonest group that infect horses. These nematodes consist of a complex tribe of 51 species, although individual horses tend to harbour 10 or so common species, in addition to a few rarer species. The Cyathostominae can be extremely pathogenic, and high levels of infection result in clinical symptoms ranging from chronic weight loss to colic, diarrhoea and death. As part of their life cycle, immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 50 publications
2
17
1
4
Order By: Relevance
“…In this study, nematodes were the predominant group of parasites found in the Przewalski's horses. Cestodes from the genus Anaplocephala, which are frequently reported from various equids including the Przewalski's horses (Nilsson et al, 1995;Williamson et al, 1997;Elias et al, 2002;Matthews et al, 2004;Slivinska and Dvojnos, 2006), were not found in our study. In our opinion, this may be due to the peculiarity of the management strategies and horse-keeping conditions in the Le Villaret reserve area, where the horses were initially kept, or because of the absence of intermediate hosts (oribatid ticks) for these cestodes in the steppe ecosystems of the Orenburg Reserve.…”
Section: Discussioncontrasting
confidence: 64%
“…In this study, nematodes were the predominant group of parasites found in the Przewalski's horses. Cestodes from the genus Anaplocephala, which are frequently reported from various equids including the Przewalski's horses (Nilsson et al, 1995;Williamson et al, 1997;Elias et al, 2002;Matthews et al, 2004;Slivinska and Dvojnos, 2006), were not found in our study. In our opinion, this may be due to the peculiarity of the management strategies and horse-keeping conditions in the Le Villaret reserve area, where the horses were initially kept, or because of the absence of intermediate hosts (oribatid ticks) for these cestodes in the steppe ecosystems of the Orenburg Reserve.…”
Section: Discussioncontrasting
confidence: 64%
“…Nematodes of the subfamily Cyathostominae are the most common equine parasites whose prevalence is estimated at 80-100% of the horse population (Lyons et al 1999, Gawor 2002, Matthews et al 2004, Kornaś et al 2007). The Cyathostominae family includes 50 species referred to as small strongylids (Lichtenfels et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…O controle desses nematóides vêm sendo feito, ao longo das décadas, através do uso de anti-helmínticos, muitas vezes de maneira indiscriminada e sem estratégias de controle adequadas. Esse fato conduziu a resistência desses à maioria dos anti-helmínticos disponíveis, principalmente, aos benzimidazóis (KAPLAN, 2002;MATTHEWS et al, 2004). Dessa forma, é muito importante a utilização de métodos alternativos que limitem o uso de anti-helmínticos, como o controle das formas de vida livre na pastagem através da coleta manual de fezes ou métodos alternativos como a utilização de fungos nematófagos (HERD, 1986;LARSEN et al, 1995;RÉDUA et al, 2002;CASTRO et al, 2003).…”
Section: Introductionunclassified